Resin Composition for Laminated Body, Laminated Body, and Liquid Packaging Bag

The use of an ethylene-based ionomer with a metal-containing carboxylate salt in the resin composition for intermediate layers of laminates addresses the challenges of heat sealing and temperature stability, enabling high-speed filling of laminates and liquid packaging bags over a wide temperature range.

JP7647228B2Active Publication Date: 2025-03-18JAPAN POLYETHYLENE CORP
View PDF 34 Cites 0 Cited by

Patent Information

Application Number
JP2021053580
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-26
Publication Date
2025-03-18
Estimated Expiration
2041-03-26

AI Technical Summary

Technical Problem

Conventional resin compositions for laminates and liquid packaging bags face challenges in achieving high-speed filling over a wide temperature range due to issues with heat sealing strength, hot tackability, and compatibility with automatic filling machines.

Method used

A resin composition for intermediate layers of laminates, featuring an ethylene-based ionomer where the ester group of ethylene/unsaturated carboxylic acid ester copolymer is converted to a metal-containing carboxylate salt, providing enhanced mechanical properties and temperature stability.

Benefits of technology

The proposed resin composition ensures high pressure resistance and allows for high-speed filling over a wide sealing temperature range, improving the suitability of laminates and liquid packaging bags for automatic filling machines without compromising the integrity of the packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007647228000019
    Figure 0007647228000019
  • Figure 0007647228000020
    Figure 0007647228000020
  • Figure 0007647228000001
    Figure 0007647228000001
Patent Text Reader

Abstract

To provide a resin composition for laminates, a laminate and a liquid wrapper which allow quick filling in a wide temperature range from low to high temperatures.SOLUTION: A resin composition for an intermediate layer of a laminate comprises at least (I) a substrate layer, (II) an intermediate layer and (III) a sealant layer in the stated order, the resin composition comprising an ethylenic ionomer satisfying the condition (a): a phase angle δ is 50-75 degrees at an absolute complex elastic modulus G*=0.1 MPa measured with a rotary rheometer.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate using a novel ionomer, in particular to a resin composition for an intermediate layer of the laminate, a laminate, and a liquid packaging bag. [Background technology]

[0002] Conventionally, polyamide resins, polyethylene terephthalate resins, polypropylene resins, etc., which are excellent in transparency and mechanical strength, have been used as packaging substrates. However, these resins have problems such as high heat sealing temperatures, which make it impossible to increase the packaging speed, deterioration of the packaging appearance due to shrinkage of the film during heat sealing, and low heat sealing strength. For this reason, these substrates are rarely used alone, and usually, composite films are used in which these substrates are used as substrates for lamination and a heat seal layer obtained by laminating a polyethylene resin or the like thereon is provided. For example, composite films in which a sealant layer is provided on a surface substrate layer, or packaging films obtained by laminating various intermediate layers on a substrate and further laminating a sealant layer thereon, are known as substrates for liquid packaging.

[0003] Low-density polyethylene (LDPE) and ethylene-vinyl acetate copolymer (EVA) were initially used as films for the sealant layers of such composite films. However, although LDPE film has excellent high-speed formability (processability), it has shortcomings in low-temperature heat sealability, heat resistance, and hot tackiness, while EVA has excellent low-temperature heat sealability but has shortcomings in heat resistance and hot tackiness.

[0004] In order to improve these problems, Patent Document 1 describes a method for forming a cellulose acylate having specific physical properties on a substrate layer, the density of which is 0.910 to 0.940 g / cm. 3 A composite film has been proposed in which a sealant layer made of a blend composition of a random copolymer of ethylene and an α-olefin having 4 to 10 carbon atoms and high-pressure low-density polyethylene (hereinafter sometimes abbreviated as HPLD) is laminated. In addition, Patent Document 2 proposes a blend composition of a copolymer of ethylene and an α-olefin having 3 to 18 carbon atoms, which exhibits specific temperature rising elution fractionation (hereinafter sometimes abbreviated as TREF) characteristics produced by a metallocene catalyst, and a specific low-density polyethylene, as a laminate composition that maintains the heat seal strength and hot tackiness of the above composite film and further improves the low-temperature heat sealability. In addition, Patent Document 3 proposes a polyethylene composition for a similar composite film, which is produced by a metallocene catalyst and has a density of 0.880 to 0.930 g / cm. 3 A composition has been proposed which is made of a random copolymer of ethylene and an α-olefin having 4 to 10 carbon atoms, the random copolymer having a molecular weight distribution of 1.5 to 4.0, and a high-pressure low-density polyethylene.

[0005] The sealant layer made of the blend composition of the specific ethylene-α-olefin random copolymer and high-pressure low-density polyethylene as described above has superior heat seal strength and hot tackiness, etc., compared to conventional sealant layers made of low-density polyethylene. However, in the case of packaging liquids such as soup, sauce, sauce, noodle soup, etc., the composite film (packaging material) is sealed vertically and horizontally using an automatic filling machine such as a die roll type, so that the filled bag is formed by sealing the material between two rotating rolls. When a sealant made of the blend composition described above is used in such a heat sealing method, there is a problem that the heat seal part is thinned, causing the bag to break, or the base material and the sealant layer to peel off.

[0006] In order to solve such problems, Patent Document 4 proposes a multilayer film in which an intermediate layer is provided between the substrate and the sealant layer. In such a multilayer film consisting of an outer layer (A), an intermediate layer (B), and an inner layer (C), the outer layer (A) and the inner layer (C) are made of ethylene-α-olefin copolymer (1), and the intermediate layer (B) is made of ethylene-α-olefin copolymer (1) having a density of at least 0.003 g / cm. 3It has been proposed to prepare a coextruded multilayer film for lamination using a resin composition consisting of an ethylene-α-olefin copolymer (2) having a high density, an ethylene-α-olefin copolymer (3) having a density equal to or lower than that of the ethylene-α-olefin copolymer (1), and a low-density polyethylene obtained by a high-pressure radical polymerization method.

[0007] In addition, in Patent Document 5, at least a base layer, an intermediate layer, and a sealant layer are laminated in this order in a multilayer film, and the intermediate layer is made of a resin composition having a linear low-density polyethylene (A) and a high-pressure low-density polyethylene (B) in a mixing ratio [(A) / (B)] of 70 / 30 to 40 / 60, the linear low-density polyethylene (A) being a copolymer of ethylene and an α-olefin having 4 or more carbon atoms, and having a melt flow rate of 1 to 50 g / 10 min and a density of 0.890 to 0.930 g / cm. 3 It has been proposed to use a high-pressure low-density polyethylene (B) having a molecular weight distribution, Mw / Mn, of 1.5 to 4.0 and a melt tension of 2 g or more.

[0008] Furthermore, Patent Document 6 proposes using a resin composition containing 50 to 95% by weight of linear low-density polyethylene (A) produced using a metallocene catalyst and 50 to 5% by weight of high-pressure low-density polyethylene (B) as the intermediate layer of a multilayer film in which at least a base layer, an intermediate layer, and a sealant layer are laminated in this order.

[0009] Furthermore, Patent Documents 7 and 8 propose a packaging film having an extruded three-layer structure consisting of a sealant layer made of linear low-density polyethylene (L-LDPE), an intermediate layer made of L-LDPE having a higher density than the sealant layer, and a base film layer made of a biaxially oriented film.

[0010] Furthermore, Patent Document 9 proposes a laminate in which a base film, a support layer, and a sealant layer are laminated in this order, in which the support layer is made of a linear low-density polyethylene resin polymerized using a Ziegler-Natta catalyst or a metallocene single-site catalyst, and the sealant layer is made of a composition in which two or more specific resins are blended.

[0011] However, when producing film using an automatic filling device, the setting conditions of the filling device must be adjusted to accommodate various contents and differences in base materials. Conventional films such as those disclosed in Patent Documents 1 to 9 above have problems such as an insufficient tolerance range for each individual packaging material, which makes it necessary to search for the filling conditions each time, resulting in a hassle. Further improvements in filling suitability were required.

[0012] On the other hand, ethylene-based ionomers are resins that use ethylene-unsaturated carboxylic acid copolymers as a base resin and are intermolecularly bonded with metal ions such as sodium and zinc, as described in Patent Document 10. They are characterized by their toughness, elasticity, flexibility, abrasion resistance, transparency, etc. Currently, commercially available ethylene-based ionomers include "Surlyn (registered trademark)", a sodium salt or zinc salt of ethylene-methacrylic acid copolymer developed by Dupont, and "Himilan (registered trademark)" sold by Dow Mitsui Polychemicals.

[0013] The ethylene-unsaturated carboxylic acid copolymers used as the base resins for these currently commercially available ethylene-based ionomers all use polar group-containing olefin copolymers obtained by polymerizing ethylene and polar group-containing monomers such as unsaturated carboxylic acids by high-pressure radical polymerization. The high-pressure radical polymerization method has the advantage that it is possible to polymerize relatively any type of polar group-containing monomer at low cost. However, the molecular structure of the polar group-containing olefin copolymer produced by the high-pressure radical polymerization method is a multi-branched molecular structure having many irregular long-chain branches and short-chain branches, as shown in the image diagram in Figure 1, and has the disadvantage of being insufficient in terms of strength.

[0014] Methods for producing polar group-containing olefin copolymers with a linear molecular structure, as shown in the image in Figure 2, have been explored using conventional polymerization methods that use catalysts. However, polar group-containing monomers are generally catalyst poisons, making polymerization difficult. In fact, it has been considered difficult for many years to obtain polar group-containing olefin copolymers with the desired physical properties using an industrially inexpensive and stable method. However, in recent years, the applicants of the present application have proposed a method for industrially and inexpensively obtaining polar group-containing olefin copolymers having a substantially linear molecular structure in a stable manner by using a new catalyst and a new production method. The applicants of the present application have reported in Patent Document 11 that they have succeeded in producing a polar group-containing olefin copolymer that serves as the base resin of an ethylene-based ionomer by producing a copolymer of ethylene and t-butyl acrylate using a late transition metal catalyst, modifying the resulting polar group-containing olefin copolymer by heat or acid treatment to form an ethylene-acrylic acid copolymer, and then reacting it with a metal ion to produce a binary ionomer. [Prior art documents] [Patent documents]

[0015] [Patent Document 1] Special Publication No. 02-004425 [Patent Document 2] Japanese Patent Application Publication No. 07-026079 [Patent Document 3] Japanese Patent Application Publication No. 8-269270 [Patent Document 4] Japanese Patent Application Publication No. 10-323948 [Patent Document 5] Japanese Patent Application Publication No. 11-010809 [Patent Document 6] JP 2001-009997 A [Patent Document 7] JP 2008-302977 A [Patent Document 8] JP 2005-289471 A [Patent Document 9] JP 2004-223728 A [Patent Document 10] U.S. Pat. No. 3,264,272 [Patent Document 11] JP 2016-79408 A Summary of the Invention [Problem to be solved by the invention]

[0016] In view of the above-mentioned problems in the conventional technology, an object of the present application is to provide a resin composition for a laminate, a laminate, and a liquid packaging bag that enable high-speed filling over a wide temperature range from low to high temperatures. [Means for solving the problem]

[0017] Means for Solving the Problems The present inventors conducted intensive research to solve the above problems, and as a result, discovered that the above problems can be solved by using, for an intermediate layer, a resin composition containing an ethylene-based ionomer in which an ester group of an ethylene / unsaturated carboxylate copolymer obtained from ethylene and an unsaturated carboxylate using a late transition metal catalyst is converted into a metal-containing carboxylate, and thus completed the present invention. That is, the gist of the present invention resides in the following inventions.

[0018] According to a first aspect of the present invention, there is provided a resin composition for an intermediate layer of a laminate having at least (I) a base layer, (II) an intermediate layer, and (III) a sealant layer in this order, characterized in that the resin composition for the intermediate layer contains an ethylene-based ionomer having the following characteristic (a): (a) Absolute value of complex modulus G measured by a rotational rheometer * = 0.1MPa, the phase angle δ is 50 degrees to 75 degrees.

[0019] The second aspect of the present invention provides a resin composition for an intermediate layer of a laminate according to the first aspect, wherein the ethylene-based ionomer is an ethylene-based ionomer obtained by converting at least a part of the carboxyl groups and / or dicarboxylic anhydride groups in a copolymer (P) containing, as essential constituent units, structural units (A) derived from ethylene and / or an α-olefin having 3 to 20 carbon atoms and structural units (B) derived from a monomer having a carboxyl group and / or a dicarboxylic anhydride group, into a metal-containing carboxylate containing at least one metal ion selected from Group 1, Group 2, or Group 12 of the periodic table.

[0020] According to the third aspect of the present invention, in the first or second aspect of the present invention, 13 The present invention provides a resin composition for an intermediate layer of a laminate, characterized in that the number of methyl branches calculated by C-NMR is 50 or less per 1,000 carbon atoms.

[0021] In addition, according to a fourth aspect of the present invention, there is provided a resin composition for an intermediate layer of a laminate, characterized in that in any one of the first to third aspects, the copolymer (P) contains 2 to 20 mol % of the structural unit (B) in the copolymer.

[0022] In addition, according to a fifth aspect of the present invention, there is provided a resin composition for an intermediate layer of a laminate, characterized in that in any one of the first to fourth aspects, the structural unit (A) is a structural unit derived from ethylene.

[0023] In addition, according to a sixth aspect of the present invention, there is provided a resin composition for an intermediate layer of a laminate, characterized in that in any one of the first to fifth aspects, the copolymer (P) is produced using a transition metal catalyst containing a transition metal of Groups 8 to 11 of the periodic table.

[0024] In addition, according to a seventh aspect of the present invention, there is provided a resin composition for an intermediate layer of a laminate, characterized in that in the sixth aspect, the transition metal catalyst is a transition metal catalyst comprising a phosphorus sulfonic acid or phosphorus phenol ligand and nickel or palladium.

[0025] Furthermore, according to an eighth aspect of the present invention, there is provided a laminate comprising at least (I) a base layer, (II) an intermediate layer, and (III) a sealant layer laminated in this order, and the (II) intermediate layer contains the resin composition for an intermediate layer of the laminate described in any one of the first to seventh aspects.

[0026] Furthermore, according to a ninth aspect of the present invention, there is provided a liquid packaging bag using the laminate in the eighth aspect. Effect of the Invention

[0027] In a laminate used for liquid packaging bags in an automatic filling machine, the resin composition for a laminate containing the ionomer of the present invention, which has a substantially linear structure, is used as an intermediate layer, so that the pressure resistance is high, enabling high-speed filling over a wide sealing temperature range from low to high temperatures, and satisfying the above-mentioned suitability for automatic filling. Furthermore, liquid packaging bags using this laminate do not break and can be filled with liquid at high speeds using an automatic filling machine. [Brief description of the drawings]

[0028] [Figure 1] 1 is a conceptual diagram of the molecular structure of a multi-branched polar group-containing olefin copolymer produced by high-pressure radical polymerization. The circles in the diagram represent polar groups. [Diagram 2] 1 is a conceptual diagram of a linear olefin copolymer containing a polar group, in which the circles represent polar groups. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] The present invention relates to a resin composition for laminates, which is characterized in that it constitutes the (II) intermediate layer in a laminate having three or more layers with at least an intermediate layer in the middle, particularly a laminate having at least (I) a base layer, (II) an intermediate layer, and (III) a sealant layer in this order, and contains a specific ionomer; and also to a laminate and a liquid packaging bag using the same.

[0030] The ionomer, the resin composition for laminate containing the ionomer, the laminate, and the liquid packaging bag according to the present invention will be described in detail below. In this specification, "(meth)acrylic acid" means acrylic acid or methacrylic acid. In this specification, "to" indicating a numerical range is used to mean that the numerical values ​​before and after it are included as the lower and upper limits. In this specification, a copolymer means a binary or higher copolymer containing at least one type of unit (A) and at least one type of unit (B). In addition, in this specification, the ionomer refers to an ionomer of a binary or higher copolymer that contains the structural unit (A) and a structural unit (B') in which at least a portion of the structural unit (B) is converted to a metal-containing carboxylate, and may further contain the structural unit (B).

[0031] 1. Ionomer The ionomer used in the present invention has an absolute complex modulus G measured by a rotational rheometer. * = 0.1 MPa, the phase angle δ is 50 degrees to 75 degrees, and the ionomer is substantially linear. Here, the "ethylene-based ionomer" means a polymer obtained by a polymerization reaction of carbon-carbon double bonds and at least a part of which contains a metal-containing carboxylate structure. More specifically, the ionomer used in the present invention is characterized in that at least a part of the carboxyl groups and / or dicarboxylic anhydride groups in the copolymer (P) containing, as essential constituent units, structural units (A) derived from ethylene and / or an α-olefin having 3 to 20 carbon atoms and structural units (B) derived from a monomer having a carboxyl group and / or a dicarboxylic anhydride group is converted to a metal-containing carboxylate containing at least one metal ion selected from Groups 1, 2, and 12 of the periodic table.

[0032] (1) Structural unit (A) The structural unit (A) is derived from one or more monomers selected from ethylene and α-olefins having 3 to 20 carbon atoms. The α-olefins of the present invention have the structural formula: CH2=CHR 1 is an α-olefin having 3 to 20 carbon atoms (R 1 is a hydrocarbon group having 1 to 18 carbon atoms, which may have a linear structure or may be branched.) The α-olefin more preferably has 3 to 12 carbon atoms.

[0033] Specific examples of the structural unit (A) include structural units derived from ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 3-methyl-1-butene, and 4-methyl-1-pentene, and may be a structural unit derived from ethylene. The structural unit (A) may be of one type or of multiple types. Combinations of the two types include structural units derived from ethylene-propylene, ethylene-1-butene, ethylene-1-hexene, ethylene-1-octene, propylene-1-butene, propylene-1-hexene, and propylene-1-octene. Examples of combinations of the three types include structural units derived from ethylene-propylene-1-butene, ethylene-propylene-1-hexene, ethylene-propylene-1-octene, propylene-1-butene-hexene, and propylene-1-butene-1-octene.

[0034] In the present invention, the structural unit (A) preferably essentially contains a structural unit derived from ethylene, and may further contain, as necessary, one or more structural units derived from an α-olefin having 3 to 20 carbon atoms. The amount of the structural unit derived from ethylene in the structural unit (A) may be 65 to 100 mol % or 70 to 100 mol % based on the total moles of the structural unit (A). From the standpoint of impact resistance, the structural unit (A) may be a structural unit derived from ethylene.

[0035] (2) Structural unit (B) The structural unit (B) is a structural unit derived from a monomer having a carboxy group and / or a dicarboxylic anhydride group. Note that the structural unit (B) has the same structure as the structural unit derived from a monomer having a carboxy group and / or a dicarboxylic anhydride group, and as described later in the production method, it does not necessarily have to be produced using a monomer having a carboxy group and / or a dicarboxylic anhydride group. Specific examples of monomers having a carboxy group include unsaturated carboxylic acids such as acrylic acid, methacrylic acid, maleic acid, fumaric acid, tetrahydrophthalic acid, itaconic acid, citraconic acid, crotonic acid, isocrotonic acid, norbornene dicarboxylic acid, and bicyclo[2,2,1]hept-2-ene-5,6-dicarboxylic acid. Examples of monomers having a dicarboxylic acid anhydride group include maleic anhydride, itaconic anhydride, citraconic anhydride, tetrahydrophthalic anhydride, 5-norbornene-2,3-dicarboxylic anhydride, 3,6-epoxy-1,2,3,6-tetrahydrophthalic anhydride, and tetracyclo[6.2.1.1 3,6 .0 2,7 ] Unsaturated dicarboxylic acid anhydrides such as dodec-9-ene-4,5-dicarboxylic acid anhydride and 2,7-octadien-1-yl succinic acid anhydride are exemplified. As the structural unit derived from a monomer having a carboxy group and / or a dicarboxylic acid anhydride group, from the viewpoint of industrial availability, preferably, a structural unit derived from acrylic acid, methacrylic acid, or 5-norbornene-2,3-dicarboxylic acid anhydride is mentioned, and in particular, a structural unit derived from acrylic acid may be used. Furthermore, the structural unit derived from a monomer having a carboxy group and / or a dicarboxylic anhydride group may be of one type or of multiple types.

[0036] In addition, the dicarboxylic anhydride group may react with moisture in the air to open the ring and become a part of the dicarboxylic acid, but the dicarboxylic anhydride group may be in a ring-opened state as long as it does not deviate from the gist of the present invention.

[0037] (3) Copolymer (P) The copolymer (P) used in the present invention as the base resin of the ionomer contains, as essential constituent units, structural units (A) derived from ethylene and / or an α-olefin having 3 to 20 carbon atoms and structural units (B) derived from a monomer having a carboxyl group and / or a dicarboxylic anhydride group, which are copolymerized substantially linearly, preferably randomly. Here, "substantially linear" refers to a state in which the copolymer has no branch or the frequency of branched structures is low, and the copolymer can be considered to be linear. Specifically, it refers to a state in which the phase angle δ of the copolymer is 50 degrees or more under the conditions described below.

[0038] The copolymer according to the present invention must contain at least one type of structural unit (A) and at least one type of structural unit (B), and must contain at least two types of monomer units in total, and may contain any structural unit other than (A) and (B). The any monomer used may be used alone or in combination of two or more types. The structural units and the amounts of the structural units in the copolymer according to the present invention will be described below. A structure derived from one molecule each of ethylene and / or an α-olefin having 3 to 20 carbon atoms (A), a monomer having a carboxyl group and / or a dicarboxylic anhydride group (B), and any monomer other than (A) and (B) is defined as one structural unit in the copolymer. The amount of structural units is the ratio of each structural unit expressed in mol % when all structural units in the copolymer are taken as 100 mol %.

[0039] Amount of structural units of ethylene and / or α-olefin having 3 to 20 carbon atoms (A): The structural unit amount of the structural unit (A) according to the present invention is selected from the following: lower limit is 60.0 mol% or more, preferably 70.0 mol% or more, more preferably 80.0 mol% or more, even more preferably 85.0 mol% or more, still more preferably 90.0 mol% or more, and particularly preferably 91.2 mol% or more, and upper limit is 97.9 mol% or less, preferably 97.5 mol% or less, more preferably 97.0 mol% or less, and even more preferably 96.5 mol% or less. If the amount of structural units derived from ethylene and / or an α-olefin (A) having 3 to 20 carbon atoms is less than 60.0 mol%, the toughness of the copolymer will be inferior, and if it is more than 97.9 mol%, the crystallinity of the copolymer will be high, and the transparency may be deteriorated.

[0040] Amount of structural units of monomer (B) having a carboxyl group and / or a dicarboxylic anhydride group: The amount of the structural unit (B) according to the present invention is selected from the following: the lower limit is 2.0 mol% or more, preferably 2.9 mol% or more, and more preferably 5.2 mol% or more, and the upper limit is 20.0 mol% or less, preferably 15.0 mol% or less, more preferably 10.0 mol% or less, even more preferably 8.0 mol% or less, particularly preferably 6.0 mol% or less, and most preferably 5.6 mol% or less. If the amount of structural units derived from monomer (B) having a carboxyl group and / or a dicarboxylic anhydride group is less than 2.0 mol%, the copolymer may not have sufficient adhesion to different materials having high polarity, and if it exceeds 20.0 mol%, the copolymer may not have sufficient mechanical properties. Furthermore, the monomer having a carboxyl group and / or a dicarboxylic anhydride group to be used may be used alone or in combination of two or more kinds.

[0041] Number of branches per 1,000 carbons in copolymer: In the copolymer of the present invention, in order to increase the elastic modulus and obtain sufficient mechanical properties, 13The number of methyl branches calculated by C-NMR may be 50 or less, 5 or less, 1 or less, or 0.5 or less per 1,000 carbons, with no particular limit on the lower limit, and the smaller the better. The number of ethyl branches may be 3.0 or less, 2.0 or less, 1.0 or less, or 0.5 or less per 1,000 carbons, with no particular limit on the lower limit, and the smaller the better. The number of butyl branches may be 7.0 or less, 5.0 or less, 3.0 or less, or 0.5 or less per 1,000 carbons, with no particular limit on the lower limit, and the smaller the better.

[0042] Method for measuring the amount of structural units derived from monomers having a carboxy group and / or a dicarboxylic anhydride group in a copolymer and the number of branches: The amount of structural units derived from monomers having a carboxy group and / or a dicarboxylic anhydride group in the copolymer of the present invention and the number of branches per 1,000 carbon atoms are 13 It can be determined using C-NMR spectroscopy. 13 C-NMR is measured by the following method. 200-300 mg of sample is placed in an NMR sample tube with an inner diameter of 10 mm together with 2.4 ml of a mixed solvent of o-dichlorobenzene (C6H4Cl2) and deuterated bromide benzene (C6D5Br) (C6H4Cl2 / C6D5Br = 2 / 1 (volume ratio)) and hexamethyldisiloxane, a chemical shift standard substance, and the tube is sealed after replacing with nitrogen. It is heated and dissolved to prepare a homogeneous solution, which is used as the NMR measurement sample. NMR measurements are performed at 120°C using an AV400M NMR instrument from Bruker Japan Ltd. equipped with a 10 mmφ cryoprobe. 13 C-NMR was measured using the inverse gate decoupling method with a sample temperature of 120°C, a pulse angle of 90°, a pulse interval of 51.5 seconds, and an accumulation count of 512 or more. The chemical shifts are those of hexamethyldisiloxane. 13 The C signal was set to 1.98 ppm, and the other 13The chemical shifts of the C signals are based on this. Obtained 13 In C-NMR, the amount of structural units of each monomer in the copolymer and the number of branches can be analyzed by identifying signals specific to the monomers or branches contained in the copolymer and comparing their intensities. The positions of signals specific to the monomers or branches can be referred to publicly known materials or can be independently identified depending on the sample. Such analytical techniques are commonly known to those skilled in the art.

[0043] Weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn): The weight average molecular weight (Mw) of the copolymer of the present invention has a lower limit of usually 1,000 or more, preferably 6,000 or more, and more preferably 10,000 or more, from the viewpoint of ensuring sufficient physical properties such as mechanical strength and impact resistance, and has an upper limit of usually 2,000,000 or less, preferably 1,500,000 or less, more preferably 1,000,000 or less, even more preferably 800,000 or less, and most preferably 100,000 or less, from the viewpoint of preventing the melt viscosity of the copolymer from becoming too high and facilitating molding processability. If the Mw is less than 1,000, the physical properties such as mechanical strength and impact resistance of the copolymer will be insufficient, whereas if the Mw exceeds 2,000,000, the melt viscosity of the copolymer will be extremely high, making it difficult to mold the copolymer.

[0044] The ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of the copolymer of the present invention has a lower limit of usually 1.5 or more, preferably 1.6 or more, and more preferably 1.9 or more, from the viewpoint of ensuring sufficient processability including molding of the copolymer and ionomer, and has an upper limit of usually 4.0 or less, preferably 3.5 or less, and more preferably 2.3 or less, from the viewpoint of the mechanical properties of the copolymer and ionomer. In the present invention, (Mw / Mn) may be expressed as a molecular weight distribution parameter.

[0045] The weight average molecular weight (Mw) and number average molecular weight (Mn) of the copolymer according to the present invention are determined by gel permeation chromatography (GPC). The molecular weight distribution parameter (Mw / Mn) is calculated by determining the number average molecular weight (Mn) by gel permeation chromatography (GPC) and then calculating the ratio of Mw to Mn, Mw / Mn.

[0046] An example of the GPC measurement method according to the present invention is as follows. (Measurement conditions) Machine used: Waters 150C Detector: FOXBORO MIRAN1A IR detector (measurement wavelength: 3.42 μm) Measurement temperature: 140℃ Solvent: orthodichlorobenzene (ODCB) Column: Showa Denko AD806M / S (3 columns) Flow rate: 1.0mL / min Injection volume: 0.2mL (Sample preparation) A 1 mg / mL solution of the sample is prepared using ODCB (containing 0.5 mg / mL BHT (2,6-di-t-butyl-4-methylphenol)), and dissolved at 140° C. for about 1 hour. (Calculation of molecular weight (M)) The standard polystyrene method is used, and the conversion from retention volume to molecular weight is performed using a calibration curve of standard polystyrene that has been prepared in advance. The standard polystyrene used is, for example, Tosoh's (F380, F288, F128, F80, F40, F20, F10, F4, F1, A5000, A2500, A1000) brand, Showa Denko's monodisperse polystyrene (S-7300, S-3900, S-1950, S-1460, S-1010, S-565, S-152, S-66.0, S-28.5, S-5.05, each 0.07 mg / ml solution), etc. A calibration curve is prepared by injecting 0.2 mL of a solution in which each is dissolved in ODCB (containing 0.5 mg / mL BHT) so that the concentration is 0.5 mg / mL. The calibration curve is a cubic equation obtained by approximating with the least squares method. The viscosity equation [η] = K × Mα used for conversion to molecular weight (M) uses the following values. Polystyrene (PS): K = 1.38 x 10 -4 , α=0.7 Polyethylene (PE): K = 3.92 x 10 -4 , α=0.733 Polypropylene (PP): K = 1.03 x 10 -4 , α=0.78

[0047] Melting point (Tm, ℃): The melting point of the copolymer of the present invention is indicated by the maximum peak temperature of the endothermic curve measured by a differential scanning calorimeter (DSC). When multiple peaks are shown in the endothermic curve obtained by DSC measurement, with heat flow (mW) on the vertical axis and temperature (°C) on the horizontal axis, the maximum peak temperature refers to the temperature of the peak that is the maximum height from the baseline among the multiple peaks, or when there is only one peak, the maximum peak temperature refers to the temperature of that peak. From the viewpoint of heat resistance, the melting point of the copolymer of the present invention is preferably 50°C or higher, more preferably 60°C or higher, and even more preferably 70°C or higher, and from the viewpoint of obtaining sufficient adhesiveness, the upper limit is preferably 140°C or lower, more preferably 138°C or lower, and even more preferably 135°C or lower. In the present invention, the melting point can be determined from the absorption curve obtained by, for example, using a DSC (DSC7020) manufactured by SII Nano Technology Inc., packing about 5.0 mg of a sample into an aluminum pan, heating it to 200°C at 10°C / min, holding it isothermally at 200°C for 5 minutes, lowering it to 20°C at 10°C / min, holding it isothermally at 20°C for 5 minutes, and then heating it again to 200°C at 10°C / min.

[0048] Crystallinity (%): In the copolymer of the present invention, the crystallinity observed by differential scanning calorimetry (DSC) is not particularly limited, but is preferably more than 0% and not more than 30%, more preferably more than 0% and not more than 25%, particularly preferably more than 5% and not more than 25%, and most preferably 7% or more and not more than 24%. In the present invention, the crystallinity can be determined, for example, by determining the heat of fusion (ΔH) from the area of ​​the melting endothermic peak obtained by DSC measurement using the same procedure as in the measurement of the melting point, and dividing the heat of fusion by the heat of fusion of 293 J / g of perfect crystals of high density polyethylene (HDPE).

[0049] Molecular structure of copolymer: The molecular chain terminals of the copolymer according to the present invention may be structural units (A) of ethylene and / or an α-olefin having 3 to 20 carbon atoms, structural units (B) of a monomer having a carboxyl group and / or a dicarboxylic anhydride group, or structural units of any monomer other than (A) and (B).

[0050] The copolymer according to the present invention may be a random copolymer, block copolymer, graft copolymer, etc., of a structural unit (A) of ethylene and / or an α-olefin having 3 to 20 carbon atoms, a structural unit (B) of a monomer having a carboxyl group and / or a dicarboxylic anhydride group, and any monomer. Among these, a random copolymer that can contain a large amount of the structural unit (B) may be used. An example of the molecular structure of a typical ternary copolymer (1) is shown below. A random copolymer is a copolymer in which the probability of finding a structural unit (A) of ethylene and / or an α-olefin having 3 to 20 carbon atoms, a structural unit (B) of a monomer having a carboxyl group and / or a dicarboxylic anhydride group, and a structural unit (C) of an arbitrary monomer at a position in an arbitrary molecular chain, as shown in the molecular structure example (1) below, is independent of the type of the adjacent structural unit. As shown below, in the molecular structure example (1) of the copolymer, a structural unit (A) of ethylene and / or an α-olefin having 3 to 20 carbon atoms, a structural unit (B) of a monomer having a carboxyl group and / or a dicarboxylic anhydride group, and a structural unit (C) of an arbitrary monomer form a random copolymer. [ka]

[0051] For reference, an example of a molecular structure (2) of a copolymer into which structural unit (B) of a monomer having a carboxyl group and / or a dicarboxylic anhydride group has been introduced by graft modification is shown. A part of a copolymer in which structural unit (A) of ethylene and / or an α-olefin having 3 to 20 carbon atoms and structural unit (C) of an arbitrary monomer are copolymerized is graft modified with structural unit (B) of a monomer having a carboxyl group and / or a dicarboxylic anhydride group. [ka]

[0052] In addition, the random copolymerization of a copolymer can be confirmed by various methods, but a method for determining the random copolymerization from the relationship between the comonomer content and melting point of the copolymer is described in detail in JP 2015-163691 A and JP 2016-079408 A. From the above documents, it can be determined that the randomness is low when the melting point (Tm, °C) of the copolymer is higher than -3.74 × [Z] + 130 (where [Z] is the comonomer content / mol%).

[0053] The copolymer according to the present invention preferably has a melting point (Tm, °C) measured by differential scanning calorimetry (DSC) and a total content [Z] (mol %) of the structural unit (B) of the monomer having a carboxyl group and / or a dicarboxylic anhydride group and the structural unit (C) of an arbitrary monomer, which satisfy the following formula (I): 50 <Tm<-3.74×[Z]+130···(I) If the melting point of the copolymer (Tm, °C) is higher than -3.74 × [Z] + 130 (°C), the random copolymerization is low, resulting in poor mechanical properties such as impact strength. If the melting point is lower than 50°C, the heat resistance may be poor.

[0054] Furthermore, the copolymer according to the present invention is preferably produced in the presence of a transition metal catalyst, from the viewpoint of making the molecular structure thereof linear. It is known that the molecular structure of the copolymer varies depending on the production method, such as polymerization by a high-pressure radical polymerization process or polymerization using a metal catalyst. The difference in molecular structure can be controlled by selecting the production method, but the molecular structure can also be estimated from the complex modulus measured with a rotational rheometer, as described in JP 2010-150532 A, for example.

[0055] · Absolute value of complex elastic modulus G * Phase angle δ at =0.1MPa: In the copolymer of the present invention, the absolute value of the complex modulus G measured by a rotational rheometer * The phase angle δ at σ = 0.1 MPa may have a lower limit of 50 degrees or more, 51 degrees or more, 54 degrees or more, 56 degrees or more, or 58 degrees or more, and an upper limit of 75 degrees or less, or 70 degrees or less. More specifically, the absolute value of the complex modulus G measured by a rotational rheometer * = Phase angle δ at 0.1 MPa (G * =0.1 MPa) is 50 degrees or more, the molecular structure of the copolymer is a linear structure containing no long chain branches or a substantially linear structure containing a small amount of long chain branches that does not affect the mechanical strength. In addition, the absolute value of the complex modulus G measured by a rotational rheometer * = Phase angle δ at 0.1 MPa (G * = 0.1 MPa) is lower than 50 degrees, the molecular structure of the copolymer will contain excessive long chain branches, resulting in poor mechanical strength. Absolute value of complex modulus G measured by a rotational rheometer * The phase angle δ at G = 0.1 MPa is affected by both the molecular weight distribution and long chain branching. However, for copolymers with Mw / Mn ≦ 4, more preferably Mw / Mn ≦ 3, it is an index of the amount of long chain branching, and the more long chain branches there are in the molecular structure, the lower the δ(G *If the Mw / Mn of the copolymer is 1.5 or more, the δ(G * =0.1MPa) value never exceeds 75 degrees.

[0056] In the present invention, the method for measuring the complex elastic modulus is as follows. The sample is placed in a 1.0 mm thick heat press mold and preheated for 5 minutes in a heat press machine with a surface temperature of 180°C. The residual gas in the molten resin is degassed by repeatedly applying and depressurizing pressure, and then the sample is pressurized to 4.9 MPa and held for 5 minutes. The sample is then transferred to a press machine with a surface temperature of 25°C and cooled by holding at a pressure of 4.9 MPa for 3 minutes to create a press plate made of the sample with a thickness of approximately 1.0 mm. The press plate made of the sample is processed into a circle with a diameter of 25 mm to use as a sample. A Rheometrics ARES type rotational rheometer is used as a measuring device for dynamic viscoelastic properties, and dynamic viscoelasticity is measured under the following conditions in a nitrogen atmosphere. Plate: φ25mm parallel plate ·Temperature: 160℃ Distortion: 10% Measurement angular frequency range: 1.0×10 -2 ~1.0×10 2 rad / s Measurement interval: 5 points / decade Absolute value of complex elastic modulus G * Common logarithm logG of (Pa) * Plot the phase angle δ against logG * = 5.0, the value of δ (degrees) at the point * = 0.1MPa). * If there is no point corresponding to =5.0, logG * Using two points around =5.0, logG * The δ value at logG = 5.0 is calculated by linear interpolation. * <5, logG * Using the three largest values, we plot logG on a quadratic curve. * = 5.0.

[0057] Regarding the production of copolymers: The copolymer according to the present invention is preferably produced in the presence of a transition metal catalyst, from the viewpoint of making the molecular structure thereof linear. Polymerization catalyst: The type of polymerization catalyst used in the production of the copolymer according to the present invention is not particularly limited as long as it is capable of copolymerizing the structural unit (A), the structural unit (B), and any structural unit. For example, a transition metal compound of Groups 5 to 11 having a chelating ligand can be used. Specific examples of preferred transition metals include vanadium atom, niobium atom, tantalum atom, chromium atom, molybdenum atom, tungsten atom, manganese atom, iron atom, platinum atom, ruthenium atom, cobalt atom, rhodium atom, nickel atom, palladium atom, copper atom, etc. Among these, preferred are transition metals of Groups 8 to 11, more preferred are transition metals of Group 10, and particularly preferred are nickel (Ni) and palladium (Pd). These metals may be used alone or in combination. Chelating ligands have at least two atoms selected from the group consisting of P, N, O, and S, and include ligands that are bidentate or multidentate, and are electronically neutral or anionic. Exemplary chelating ligand structures are given in the review by Brookhart et al. (Chem. Rev., 2000, 100, 1169). The chelating ligand preferably includes a bidentate anionic P, O ligand. Examples of the bidentate anionic P, O ligand include phosphorus sulfonic acid, phosphorus carboxylic acid, phosphorus phenol, and phosphorus enolate. Other examples of the chelating ligand include a bidentate anionic N, O ligand. Examples of the bidentate anionic N, O ligand include salicylaldimine and pyridine carboxylic acid. Other examples of the chelating ligand include a diimine ligand, a diphenoxide ligand, and a diamide ligand.

[0058] The structure of the metal complex obtained from the chelating ligand is represented by the following structural formula (a) or (b) in which an arylphosphine compound, an arylarsine compound or an arylantimony compound which may have a substituent is coordinated. [ka] [ka] [In structural formula (a) and structural formula (b), M represents a transition metal belonging to any of Groups 5 to 11 of the periodic table of the elements, that is, various transition metals as described above. X 1 represents oxygen, sulfur, -SO3-, or -CO2-. Y 1 represents carbon or silicon. n represents an integer of 0 or 1. E 1 represents phosphorus, arsenic or antimony. R 53 and R 54 each independently represents hydrogen or a hydrocarbon group having 1 to 30 carbon atoms which may contain a heteroatom. R 55 each independently represents hydrogen, halogen, or a hydrocarbon group having 1 to 30 carbon atoms which may contain a heteroatom. R 56 and R 57 each independently represents a hydrogen atom, a halogen atom, a hydrocarbon group having 1 to 30 carbon atoms which may contain a heteroatom, OR 52 , CO2R 52 , CO2M', C(O)N(R 51 )2, C(O)R 52 , S.R. 52 , SO2R 52 , SOR 52 , OSO2R 52 , P(O)(OR 52 ) 2-y (R 51 ) y , C.N., N.H.R. 52 , N(R 52)2, Si(OR 51 ) 3-x (R 51 ) x , OSi(OR 51 ) 3-x (R 51 ) x , NO2, SO3M', PO3M'2, P(O)(OR 52 )2M' or an epoxy-containing group. R 51 represents hydrogen or a hydrocarbon group having 1 to 20 carbon atoms. R 52 represents a hydrocarbon group having 1 to 20 carbon atoms. M′ represents an alkali metal, an alkaline earth metal, ammonium, a quaternary ammonium or a phosphonium; x represents an integer of 0 to 3; and y represents an integer of 0 to 2. In addition, R 56 and R 57 may be linked to each other to form an alicyclic ring, an aromatic ring, or a heterocyclic ring containing a heteroatom selected from oxygen, nitrogen, or sulfur, in which case the ring has 5 to 8 members and may or may not have a substituent on the ring. L 1 represents a ligand coordinated to M. Also, R 53 and L 1 may be bonded to each other to form a ring.

[0059] More preferably, it is a transition metal complex represented by the following structural formula (c). [ka] [In structural formula (c), M represents a transition metal belonging to any of Groups 5 to 11 of the periodic table of the elements, that is, various transition metals as described above. X 1 represents oxygen, sulfur, -SO3-, or -CO2-. Y 1 represents carbon or silicon. n represents an integer of 0 or 1. E 1represents phosphorus, arsenic or antimony. R 53 and R 54 each independently represents hydrogen or a hydrocarbon group having 1 to 30 carbon atoms which may contain a heteroatom. R 55 each independently represents hydrogen, halogen, or a hydrocarbon group having 1 to 30 carbon atoms which may contain a heteroatom. R 58 , R 59 , R 60 and R 61 each independently represents a hydrogen atom, a halogen atom, a hydrocarbon group having 1 to 30 carbon atoms which may contain a heteroatom, OR 52 , CO2R 52 , CO2M', C(O)N(R 51 )2, C(O)R 52 , S.R. 52 , SO2R 52 , SOR 52 , OSO2R 52 , P(O)(OR 52 ) 2-y (R 51 ) y , C.N., N.H.R. 52 , N(R 52 )2, Si(OR 51 ) 3-x (R 51 ) x , OSi(OR 51 ) 3-x (R 51 ) x , NO2, SO3M', PO3M'2, P(O)(OR 52 )2M' or an epoxy-containing group. R 51 represents hydrogen or a hydrocarbon group having 1 to 20 carbon atoms. R 52 represents a hydrocarbon group having 1 to 20 carbon atoms. M′ represents an alkali metal, an alkaline earth metal, ammonium, a quaternary ammonium or a phosphonium; x represents an integer of 0 to 3; and y represents an integer of 0 to 2. In addition, R 58 ~R 61may be bonded to each other to form an alicyclic ring, an aromatic ring, or a heterocyclic ring containing a heteroatom selected from oxygen, nitrogen, or sulfur. In this case, the number of ring members is 5 to 8, and the ring may or may not have a substituent. L 1 represents a ligand coordinated to M. Also, R 53 and L 1 may be bonded to each other to form a ring.

[0060] Here, typical catalysts of Group 5 to 11 transition metal compounds having a chelating ligand include so-called SHOP catalysts and Drent catalysts. The SHOP catalyst is a catalyst in which a phosphorus-based ligand having an aryl group which may have a substituent is coordinated to nickel metal (see, for example, WO2010-050256). Furthermore, the Drent catalyst is a catalyst in which a phosphorus-based ligand having an aryl group which may have a substituent is coordinated to palladium metal (see, for example, JP-A-2010-202647).

[0061] Copolymerization method: The polymerization method for the copolymer according to the present invention is not limited. Examples of the polymerization method include slurry polymerization in which at least a portion of the produced polymer becomes a slurry in a medium, bulk polymerization in which the liquefied monomer itself is used as the medium, gas phase polymerization in vaporized monomer, and high pressure ionic polymerization in which at least a portion of the produced polymer is dissolved in monomer liquefied at high temperature and pressure. The polymerization method may be any of batch polymerization, semi-batch polymerization, and continuous polymerization. Furthermore, living polymerization may be carried out, or polymerization may be carried out while simultaneously causing chain transfer. Furthermore, during polymerization, a so-called chain shuttling agent (CSA) may be used in combination to carry out a chain shuttling reaction or coordinate chain transfer polymerization (CCTP). Specific manufacturing processes and conditions are disclosed in, for example, Japanese Patent Application Laid-Open No. 2010-260913 and Japanese Patent Application Laid-Open No. 2010-202647.

[0062] Method for introducing carboxyl groups and / or dicarboxylic anhydride groups into copolymers: The method for introducing a carboxyl group and / or a dicarboxylic anhydride group into the copolymer according to the present invention is not particularly limited. Carboxyl groups and / or dicarboxylic anhydride groups can be introduced by various methods within the scope of the present invention. Examples of methods for introducing a carboxyl group and / or a dicarboxylic anhydride group include a method of directly copolymerizing a comonomer having a carboxyl group and / or a dicarboxylic anhydride group, and a method of copolymerizing another monomer and then introducing a carboxyl group and / or a dicarboxylic anhydride group by modification.

[0063] Methods for introducing a carboxyl group and / or a dicarboxylic anhydride group by modification include, for example, when introducing a carboxylic acid, a method in which an acrylic ester is copolymerized and then hydrolyzed to convert it to a carboxylic acid, and a method in which t-butyl acrylate is copolymerized and then thermally decomposed to convert it to a carboxylic acid.

[0064] A conventionally known acid-base catalyst may be used as an additive for promoting the reaction during the hydrolysis or thermal decomposition. The acid-base catalyst is not particularly limited, and examples of the acid-base catalyst that can be used include, for example, hydroxides of alkali metals or alkaline earth metals such as sodium hydroxide, potassium hydroxide, or lithium hydroxide, alkali metals or carbonates of alkaline earth metals such as sodium hydrogencarbonate or sodium carbonate, solid acids such as montmorillonite, inorganic acids such as hydrochloric acid, nitric acid, or sulfuric acid, and organic acids such as formic acid, acetic acid, benzoic acid, citric acid, paratoluenesulfonic acid, trifluoroacetic acid, or trifluoromethanesulfonic acid. From the viewpoints of reaction promotion effect, cost, equipment corrosivity, etc., sodium hydroxide, potassium hydroxide, sodium carbonate, trifluoroacetic acid, and paratoluenesulfonic acid are preferred, and trifluoroacetic acid and paratoluenesulfonic acid are more preferred.

[0065] (4) Ionomer The ionomer according to the present invention is an ionomer having a substantially linear structure in which at least a part of the carboxyl group and / or dicarboxylic anhydride group of the structural unit (B) of the copolymer of the present invention is converted to a metal-containing carboxylate containing at least one metal ion selected from Group 1, Group 2, or Group 12 of the periodic table. As described below, the ionomer is obtained by reacting an ionomer base resin with a metal salt, and during this process, a reaction that cuts the molecular chain of the polymer does not usually occur. Therefore, parameters related to the structure, such as the molar ratio of the comonomer, the degree of branching, and randomness, are usually preserved between the ionomer base resin and the ionomer.

[0066] Ionomer structure: The ionomer according to the present invention has a substantially linear structure like the copolymer according to the present invention, and therefore the absolute value of the complex modulus G measured by a rotational rheometer * The phase angle δ at pressure σ=0.1 MPa is characterized in that it is 50 degrees to 75 degrees. The lower limit of the phase angle δ may be 51 degrees or more, and the upper limit of the phase angle δ may be 64 degrees or less. Phase angle δ(G * =0.1MPa) is lower than 50 degrees, the molecular structure of the ionomer contains excessive long chain branches, resulting in poor mechanical strength. As mentioned above, if Mw / Mn≦4, the phase angle δ is an index of the amount of long chain branches. If the Mw / Mn of an ionomer is 1.5 or more, the phase angle δ(G * =0.1MPa) value never exceeds 75 degrees.

[0067] Melting point of ionomer (Tm, ℃): From the viewpoint of heat resistance, the melting point of the ionomer of the present invention is preferably, at the lower limit, 50°C or higher, more preferably 60°C or higher, and even more preferably 70°C or higher; from the viewpoint of obtaining sufficient adhesiveness, the upper limit is preferably, at the upper limit, 140°C or lower, more preferably 138°C or lower, and even more preferably 135°C or lower.

[0068] Crystallinity (%): In the ionomer of the present invention, the crystallinity observed by differential scanning calorimetry (DSC) is not particularly limited, but is preferably greater than 0% and not greater than 30%, more preferably greater than 0% and not greater than 25%, particularly preferably greater than 5% and not greater than 25%, and most preferably 7% or more and not greater than 24%. If the crystallinity is 0%, the toughness of the ionomer is insufficient, and if the crystallinity is higher than 30%, the transparency of the copolymer may be poor. Note that the crystallinity is an index of transparency, and it can be determined that the lower the crystallinity of the ionomer, the more excellent its transparency.

[0069] Metal ions: The metal ions contained in the ionomer of the present invention are not particularly limited, and may include metal ions used in conventionally known ionomers. Among them, metal ions of Groups 1, 2, or 12 of the periodic table are preferred, and Li + , Na + , K + , Rb + , Cs + , Mg 2+ , Ca 2+ , Sr 2+ , B.A. 2+ and Zn 2+ More preferably, at least one selected from the group consisting of Li + , Na + , K + , Mg 2+ , Ca 2+ , and Zn 2+ , more preferably Na + , and Zn 2+At least one selected from the group consisting of: Two or more of these metal ions may be mixed and contained as necessary.

[0070] ·Neutralization degree (mol%): The metal ion content is preferably an amount that neutralizes at least a part or all of the carboxyl groups and / or dicarboxylic anhydride groups in the copolymer as the base polymer, and the preferred degree of neutralization (average degree of neutralization) is 5 to 95 mol%, more preferably 10 to 90 mol%, and even more preferably 20 to 80 mol%. A high degree of neutralization results in an ionomer with high tensile strength and tensile stress at break, and low tensile strain at break, but the melt flow rate (MFR) of the ionomer tends to be low. On the other hand, a low degree of neutralization results in an ionomer with a moderate MFR, but low tensile modulus and tensile stress at break, and high tensile strain at break. The degree of neutralization can be determined from the ratio of the total molar amount of the valence×molar amount of the metal ion to the total molar amount of the carboxy groups that may be contained in the carboxy groups and / or dicarboxylic anhydride groups in the copolymer. When a dicarboxylic anhydride group forms a carboxylate, it opens its ring to form a dicarboxylic acid, so the total molar amount of the carboxyl groups is calculated assuming that there are 2 mol of carboxyl groups per 1 mol of dicarboxylic anhydride group. 2+ For divalent metal ions such as those mentioned above, 1 mole of each can form a salt with 2 moles of carboxyl groups, and the total molar amount of molecules with the degree of neutralization is calculated by 2 x the molar amount.

[0071] ·Ionomer manufacturing method: The ionomer according to the present invention may be obtained by subjecting a copolymer of ethylene and / or an α-olefin having 3 to 20 carbon atoms / unsaturated carboxylic acid obtained by the above-mentioned method for introducing a carboxyl group and / or a dicarboxylic anhydride group into the copolymer to a conversion step of treating the copolymer with a metal salt containing at least one metal ion selected from Group 1, Group 2, or Group 12 of the periodic table to convert the copolymer into a metal-containing carboxylate. The ionomer according to the present invention may also be obtained by subjecting a copolymer of ethylene and / or an α-olefin having 3 to 20 carbon atoms / unsaturated carboxylic acid ester to a heat conversion step of heating the copolymer to convert at least a part of the ester groups in the copolymer into a metal-containing carboxylate containing at least one metal ion selected from Group 1, Group 2, or Group 12 of the periodic table.

[0072] When an ionomer is produced after introducing a carboxyl group and / or a dicarboxylic anhydride group into a polymer, the production method is, for example, as follows: A metal ion source is prepared by kneading a metal salt with a substance that captures metal ions, such as an ethylene / methacrylic acid (MAA) copolymer, optionally with heating, and then the metal ion source is added to an ionomer base resin in an amount that results in a desired degree of neutralization, followed by kneading.

[0073] In the thermal conversion step, (i) ethylene and / or an α-olefin having 3 to 20 carbon atoms / unsaturated carboxylic acid ester copolymer may be heated to convert the copolymer into an ethylene and / or an α-olefin having 3 to 20 carbon atoms / unsaturated carboxylic acid copolymer by hydrolysis or thermal decomposition, and then the copolymer may be reacted with a compound containing a metal ion of Group 1, Group 2, or Group 12 of the periodic table to convert the carboxylic acid in the copolymer into the metal-containing carboxylate. In addition, (ii) ethylene and / or an α-olefin having 3 to 20 carbon atoms / unsaturated carboxylic acid ester copolymer may be heated to convert the ester group of the copolymer into the metal-containing carboxylate while reacting the copolymer with a compound containing a metal ion of Group 1, Group 2, or Group 12 of the periodic table to convert the ester group portion in the copolymer into the metal-containing carboxylate.

[0074] Furthermore, the compound containing a metal ion may be an oxide, hydroxide, carbonate, bicarbonate, acetate, formate, etc. of a metal of Group 1, 2, or 12 of the periodic table. The compound containing metal ions may be supplied to the reaction system in the form of particles or fine powder, or may be dissolved or dispersed in water or an organic solvent and then supplied to the reaction system, or a master batch may be prepared using an ethylene / unsaturated carboxylic acid copolymer or an olefin copolymer as a base polymer and then supplied to the reaction system. In order to ensure smooth reaction, it is preferable to prepare a master batch and supply it to the reaction system.

[0075] Furthermore, the reaction with the compound containing metal ions may be carried out by melt kneading using various types of equipment such as a vent extruder, a Banbury mixer, a roll mill, etc., and the reaction may be a batch or continuous method. Since the reaction can be carried out smoothly by discharging water and carbon dioxide gas by-produced by the reaction using a degassing device, it is preferable to carry out the reaction continuously using an extruder equipped with a degassing device such as a vent extruder. In the reaction with the compound containing metal ions, a small amount of water may be injected to promote the reaction.

[0076] The temperature at which the ethylene and / or C3-20 α-olefin / unsaturated carboxylic acid ester copolymer is heated may be any temperature at which the ester becomes a carboxylic acid, and if the heating temperature is too low, the ester is not converted to a carboxylic acid, whereas if the heating temperature is too high, decarbonylation or decomposition of the copolymer may proceed. Therefore, the heating temperature in the present invention is preferably in the range of 80°C to 350°C, more preferably 100°C to 340°C, even more preferably 150°C to 330°C, and even more preferably 200°C to 320°C.

[0077] The reaction time varies depending on the heating temperature, the reactivity of the ester group portion, etc., but is usually 1 minute to 50 hours, more preferably 2 minutes to 30 hours, even more preferably 2 minutes to 10 hours, still more preferably 2 minutes to 3 hours, and particularly preferably 3 minutes to 2 hours.

[0078] In the above steps, the reaction atmosphere is not particularly limited, but it is generally preferable to carry out the reaction under an inert gas flow. Examples of the inert gas include nitrogen, argon, and carbon dioxide. A small amount of oxygen or air may be mixed in.

[0079] The reactor used in the above step is not particularly limited, and any method can be used as long as it can substantially uniformly stir the copolymer. A glass vessel or an autoclave (AC) equipped with a stirrer may be used, or any conventionally known kneading machine such as a Brabender plastograph, a single-screw or twin-screw extruder, a high-intensity screw-type kneader, a Banbury mixer, a kneader, or a roll may be used.

[0080] Whether or not a metal ion has been introduced into an ionomer-based resin and it has become an ionomer can be confirmed by measuring the IR spectrum of the resulting resin and examining the decrease in the peak derived from the carbonyl group of the carboxylic acid (dimer). Similarly, the degree of neutralization can be confirmed by calculating from the molar ratio described above, as well as examining the decrease in the peak derived from the carbonyl group of the carboxylic acid (dimer) and the increase in the peak derived from the carbonyl group of the carboxylate salt group.

[0081] Ionomer properties: The ionomers used in the present invention, particularly ionomers suitable for liquid packaging applications, have any one or a combination of the following physical properties under the measurement conditions described in the Examples section below. MFR: In the ionomer of the present invention, the melt flow rate (MFR) at a temperature of 190° C. under a load of 2.16 kg is 0.01 to 30 g / 10 min, preferably 0.1 to 15 g / 10 min, and more preferably 0.5 to 20 g / 10 min. When the MFR of the ionomer is in this range, molding is easy.

[0082] Tensile modulus: In the ionomer of the present invention, the tensile modulus is 20 MPa or more, preferably 20 to 350 MPa, and more preferably 20 to 300 MPa. When the tensile modulus of the ionomer is within this range, the adhesion of the ionomer when formed into a laminate is good, and the ionomer can be produced without difficulty in designing the modulus of elasticity.

[0083] Tensile impact strength: The ionomer of the present invention has a tensile impact strength of 100 KJ / m 2 That's all. When the ionomer has a tensile impact strength in this range, there is little risk of breakage even if it is rubbed, etc. There is no particular upper limit to the tensile impact strength as long as it is within the range obtainable by the materials used, as determined by those skilled in the art.

[0084] 2. Resin composition for laminates Although the ionomer in the present invention can be extrusion laminated by itself due to ionic crosslinking, it may be added with other olefin polymers, rubbers, etc., as well as known additives such as anti-fogging agents, organic or inorganic fillers, antioxidants, organic or inorganic pigments, UV inhibitors, lubricants such as saturated or unsaturated fatty acid amides and metal salts of saturated or unsaturated higher fatty acids, dispersants, nucleating agents, crosslinking agents, etc., in accordance with a conventional method, to the extent that performance is not impaired, to form a resin composition. The "resin composition" here includes those in which the weight ratio of the ionomer is 100% by weight, i.e., materials consisting of the ionomer alone.

[0085] The melt flow rate (MFR) of the resin composition of the present invention is in the range of 1.0 to 100 g / 10 min, preferably in the range of 2.0 to 50 g / 10 min, and more preferably in the range of 2.0 to 20 g / 10 min. By setting the MFR in the above range, good molding processability can be obtained, such as keeping the extrusion load low and improving the extensibility, and the neck-in does not become large, and the stability of the film during film formation is improved.

[0086] The resin composition of the present invention can be blended by a known method generally used as a conventional resin composition blending method. One example of the method is to simply dry blend the ionomer and other additives that can be added. Another example is to dry blend the ionomer and various additives as desired using a mixer such as a tumbler, ribbon blender, or Henschel mixer, and then melt mix them using a known continuous melt kneader such as a single screw extruder or twin screw extruder, and extrude them to prepare pellets, thereby obtaining the resin composition.

[0087] 3.Laminate The laminate of the present invention is a laminate of at least three or more resin layers, more specifically, it has at least (I) a substrate layer, (II) an intermediate layer, and (III) a sealant layer in this order, and the intermediate layer (II) is made of the resin composition for laminates. In addition, the laminate is preferably formed by laminating the intermediate layer (II) and the sealant layer (III) on the substrate layer (I) by extrusion lamination or coextrusion lamination. By using these methods, the productivity of the laminate is excellent.

[0088] (1)(I) Base material layer (I) The substrate layer may be a film of paper, aluminum foil, cellophane, woven fabric, nonwoven fabric, or polymer, for example, a film of high density polyethylene, medium density polyethylene, low density polyethylene, ethylene-vinyl acetate copolymer, ethylene-acrylic acid ester copolymer, ionomer, polypropylene, poly-1-butene, poly-4-methylpentene-1, or other olefin polymer, polyvinyl chloride, polyvinylidene chloride, polystyrene, polyacrylate, polyacrylonitrile, or other vinyl copolymer, nylon 6, nylon 66, nylon 7, nylon 10, nylon 11, nylon 12, nylon 610, or other polyamide, polyethylene terephthalate, polyethylene terephthalate / isophthalate, polybutylene terephthalate, or other polyester, polyvinyl alcohol, ethylene-vinyl alcohol copolymer, polycarbonate, or other film. (I) The film used as the substrate layer may be one type, or two or more types. In addition, the film may be stretched depending on the type of substrate. Examples of films that have been stretched include uniaxially or biaxially stretched polypropylene films, stretched nylon films, stretched polyethylene terephthalate films, stretched polystyrene films, etc. Furthermore, the above-mentioned films may be coated with polyvinylidene chloride or polyvinyl alcohol, or may be vapor-deposited with aluminum, alumina, silica, or a mixture of alumina and silica, and may be used as the substrate layer (I). In the case of a film for packaging contents containing liquid or viscous material, the substrate layer (I) may be a biaxially stretched nylon film, a biaxially stretched polyethylene terephthalate film, or a substrate having silica or alumina vapor-deposited thereon.

[0089] (2)(III) Sealant Layer The (III) sealant layer is not particularly limited, and a conventionally known ethylene-based resin composition can be used. For example, an ethylene-α-olefin copolymer or a blend composition of an ethylene-α-olefin copolymer and HPLD can be used. Usually, examples of methods for producing laminates include dry lamination, wet lamination, extrusion, sandwich lamination, and coextrusion. For example, packaging films used for dry lamination and the like can be produced by any method such as calendaring, air-cooled inflation, water-cooled inflation, and T-die molding. In addition, in the case of extrusion methods, there are methods such as extrusion lamination, dry lamination, sandwich lamination, and coextrusion lamination (including coextrusion without an adhesive layer, coextrusion with an adhesive layer, and coextrusion with an adhesive resin).

[0090] The laminate of the present invention is not particularly limited with respect to the thickness of the entire laminate, the thickness of each layer, or the thickness ratio of each layer, and can be appropriately selected according to the contents, applications, etc. The thickness of the entire laminate is, for example, 40 to 120 μm, the thickness of the base layer is 10 to 40 μm, the thickness of the intermediate layer is 20 to 40 μm, and the thickness of the sealant layer is about 10 to 40 μm. In addition, when laminating, in order to improve the adhesion of the base surface, surface treatment such as corona discharge treatment, ozone treatment, and frame treatment can be performed on the base layer in advance. Furthermore, in order to enhance adhesion, etc., an anchor coating agent can be applied to the base before lamination. Examples of anchor coating agents include isocyanate-based, polyethyleneimine-based, and polybutadiene-based agents. The laminate of the present invention can be used as various packaging materials, such as food packaging materials, medical packaging materials, and packaging materials for industrial materials such as engine oil. In particular, it can be suitably used as a packaging material for contents containing liquids. For example, it can be used as a liquid packaging bag for containing liquids, liquids containing solid insoluble matter such as fibers and powders, and fluids such as viscous bodies as contents. EXAMPLES

[0091] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples. The physical properties in the examples and comparative examples were measured and evaluated by the methods shown below. In the tables, "no data" means that no measurement was performed, and "not detected" means that the value was below the detection limit.

[0092] 1. Measurement and Evaluation (1) Absolute value of complex elastic modulus G * Measurement of phase angle δ at 0.1 MPa 1) Sample preparation and measurement The sample was placed in a 1.0 mm thick mold for hot pressing, preheated in a hot press machine with a surface temperature of 180°C for 5 minutes, and then repeatedly pressurized and depressurized to remove residual gas in the molten resin. The sample was then pressed at 4.9 MPa and held for 5 minutes. The sample was then transferred to a press machine with a surface temperature of 25°C and cooled by holding at a pressure of 4.9 MPa for 3 minutes to produce a pressed plate made of a sample with a thickness of approximately 1.0 mm. The pressed plate made of the sample was processed into a circular shape with a diameter of 25 mm to prepare a sample. The dynamic viscoelasticity was measured under the following conditions in a nitrogen atmosphere using an ARES type rotational rheometer manufactured by Rheometrics Co., Ltd. as a measuring device for dynamic viscoelastic properties. (Measurement conditions) Plate: φ25mm (diameter) parallel plate Temperature: 160℃ Distortion: 10% Measurement angular frequency range: 1.0×10 -2 ~1.0×10 2 rad / s Measurement interval: 5 points / decade The phase angle δ is plotted against the common logarithm logG* of the absolute value of the complex elastic modulus G* (Pa), and logG * = 5.0, the value of δ (degrees) at the point * = 0.1MPa). * If there is no point corresponding to =5.0, logG * Using two points around =5.0, logG * The δ value at logG = 5.0 was calculated by linear interpolation. * <5, logG * Using the three largest values, we plot logG on a quadratic curve. * The δ value at =5.0 was extrapolated.

[0093] (2) Measurement of weight average molecular weight (Mw) and molecular weight distribution parameter (Mw / Mn) The weight average molecular weight (Mw) was determined by gel permeation chromatography (GPC). The molecular weight distribution parameter (Mw / Mn) was calculated from the ratio of Mw to Mn, Mw / Mn, obtained by further determining the number average molecular weight (Mn) by gel permeation chromatography (GPC). The measurements were carried out according to the following procedures and conditions.

[0094] 1) Sample pretreatment When the sample contained a carboxylic acid group, it was subjected to an esterification treatment, such as methyl esterification using diazomethane or trimethylsilyl (TMS) diazomethane, before use in the measurement. When the sample contained a carboxylate group, it was subjected to an acid treatment to modify the carboxylate group to a carboxylic acid group, and then subjected to the above-mentioned esterification treatment before use in the measurement.

[0095] 2) Preparation of sample solution 3 mg of sample and 3 mL of o-dichlorobenzene were weighed into a 4 mL vial, and the vial was capped with a screw cap and a Teflon (registered trademark) septum, and then shaken for 2 hours at 150°C using a Senshu Scientific SSC-7300 high-temperature shaker. After shaking, it was visually confirmed that there were no insoluble components.

[0096] 3) Measurement A Waters Alliance GPCV2000 was connected to Showa Denko's high temperature GPC columns Showdex HT-G x 1 and HT-806M x 2, and measurements were performed using o-dichlorobenzene as the eluent at a temperature of 145°C and a flow rate of 1.0 mL / min.

[0097] 4) Calibration curve The column was calibrated using monodisperse polystyrene (S-7300, S-3900, S-1950, S-1460, S-1010, S-565, S-152, S-66.0, S-28.5, S-5.05, each 0.07 mg / ml solution) manufactured by Showa Denko, n-eicosane and n-tetracontane were measured under the same conditions as above, and the elution time and the logarithm of the molecular weight were approximated by a fourth-order equation. PS ) and polyethylene molecular weight (M PE The following formula was used to convert M PE =0.468×M PS

[0098] (3) Melt flow rate (MFR) The MFR was measured in accordance with Table 1-Condition 7 of JIS K-7210 (1999) at a temperature of 190°C and a load of 21.18N (=2.16kg).

[0099] (4) Tensile test A 1 mm thick sheet was prepared as a sample by the method described in JIS K7151 (1995) (cooling method A), and this was punched out to prepare a small 5B type test piece described in JIS K7162 (1994). A tensile test was performed at a temperature of 23°C in accordance with JIS K7161 (1994) to measure the tensile modulus, tensile stress at break, and tensile strain at break. The test speed was 10 mm / min.

[0100] (5) Melting point and crystallinity The melting point is indicated by the peak temperature of the endothermic curve measured by a differential scanning calorimeter (DSC). The measurement was performed using a DSC (DSC7020) manufactured by SII Nano Technology Co., Ltd. under the following measurement conditions. Approximately 5.0 mg of the sample was packed into an aluminum pan, heated to 200°C at 10°C / min, held at 200°C for 5 minutes, and then cooled to 30°C at 10°C / min. After holding at 30°C for 5 minutes, the sample was heated again at 10°C / min. The maximum peak temperature in the absorption curve was taken as the melting point Tm, and the heat of fusion (ΔH) was calculated from the area of ​​the melting endothermic peak. The degree of crystallinity (%) was calculated by dividing the heat of fusion by the heat of fusion of perfect crystals of high density polyethylene (HDPE), 293 J / g.

[0101] (6) Method for measuring the amount of structural units derived from monomers having a carboxyl group and / or a dicarboxylic anhydride group, and non-cyclic monomers, and the number of branches per 1,000 carbon atoms The amount of structural units derived from monomers having a carboxy group and / or a dicarboxylic anhydride group and non-cyclic monomers in the copolymer of the present invention, and the number of branches per 1,000 carbon atoms are 13 It can be determined using C-NMR spectroscopy. 13 C-NMR was measured by the following method. 200-300 mg of sample was placed in an NMR sample tube with an inner diameter of 10 mm together with 2.4 ml of a mixed solvent of o-dichlorobenzene (C6H4Cl2) and deuterated bromide benzene (C6D5Br) (C6H4Cl2 / C6D5Br = 2 / 1 (volume ratio)) and hexamethyldisiloxane, a chemical shift standard substance, and the tube was purged with nitrogen, sealed, and heated to dissolve and prepare a homogeneous solution to be used as the NMR measurement sample. NMR measurements were performed at 120°C using an AV400M NMR instrument from Bruker Japan equipped with a 10 mmφ cryoprobe. 13 C-NMR was measured using the inverse gate decoupling method with a sample temperature of 120°C, a pulse angle of 90°, a pulse interval of 51.5 seconds, and an accumulation number of 512 or more. The chemical shifts are those of hexamethyldisiloxane. 13 The C signal was set to 1.98 ppm, and the other 13 The chemical shifts of the C signals were based on this.

[0102] 1) Sample pretreatment When the sample contained a carboxylate group, the sample was subjected to an acid treatment to convert the carboxylate group to a carboxyl group before the measurement. When the sample contained a carboxyl group, an esterification treatment such as methyl esterification using diazomethane or trimethylsilyl (TMS) diazomethane may be appropriately performed.

[0103] 2) Calculation of the amount of structural units derived from monomers having a carboxy group and / or a dicarboxylic anhydride group, and non-cyclic monomers The quaternary carbon signal of the t-butyl acrylate group of tBA is 13 It is detected at 79.6 to 78.8 in the C-NMR spectrum. Using these signal intensities, the amount of comonomer was calculated from the following formula. Total amount of tBA (mol%) = I(tBA) × 100 / 〔I(tBA) + I(E)〕 Here, I(tBA) and I(E) are the quantities shown in the following formulas. I(tBA)=I 79.6~78.8 I(E)=(I 180.0~135.0 +I 120.0~5.0 -I(tBA) × 7) / 2

[0104] In addition, when the structural unit amount of each monomer is indicated by "<0.1" including an inequality sign, it means that it is present as a structural unit in the copolymer, but the amount is less than 0.1 mol %, taking into account significant digits.

[0105] 3) Calculation of the number of branches per 1,000 carbon atoms Copolymers come in three types: isolated types, in which a branch exists alone in the main chain, complex types (face-to-face types in which branches face each other via the main chain, branched-branch types, in which there are branches within a branched chain, and chain types). The following is an example of the structure of an ethyl branch. In the example of the facing type, R represents an alkyl group.

[0106] [ka]

[0107] The number of branches per 1,000 carbons is calculated by substituting either I(B1), I(B2), or I(B4) below into the I (branch) term in the following formula. B1 represents methyl branches, B2 represents ethyl branches, and B4 represents butyl branches. The number of methyl branches is calculated using I(B1), the number of ethyl branches using I(B2), and the number of butyl branches using I(B4). Number of branches (per 1,000 carbons) = I (branches) x 1000 / I (total) Here, I(total), I(B1), I(B2), and I(B4) are quantities expressed by the following formulas. I(total)=I 180.0~135.0 +I 120.0~5.0 I(B1)=(I 20.0~19.8 +I 33.2~33.1 +I 37.5~37.3 ) / 4 I(B2)=I 8.6~7.6 +I 11.8~10.5 I(B4)=I 14.3~13.7 -I 32.2~32.0 Here, I is the integrated intensity, and the subscripts of I indicate the range of chemical shifts. For example, I 180.0~135.0 was detected between 180.0 ppm and 135.0 ppm. 13 C The integrated intensity of the signal is shown. The attribution was based on the non-patent literature Macromolecules 1984, 17, 1756-1761 and Macromolecules 1979, 12, 41. In addition, when the number of branches is indicated as "<0.1" including an inequality sign, it means that it exists as a structural unit in the copolymer, but the amount is less than 0.1 mol% considering significant figures. Also, "not detected" means below the detection limit.

[0108] (7) Infrared absorption spectrum The sample was melted at 180° C. for 3 minutes and compression molded to prepare a film with a thickness of about 50 μm. This film was analyzed by Fourier transform infrared spectroscopy to obtain an infrared absorption spectrum. (Measurement conditions) Product name: FT / IR-6100 manufactured by JASCO Corporation Measurement method: transmission method Detector: TGS (Triglycine sulfate) Number of times: 16 to 512 Resolution: 4.0cm -1 Measurement wavelength: 5000~500cm -1

[0109] (8) Tensile impact strength 1) How to prepare samples for tensile impact strength test The sample was placed in a 1 mm thick mold for hot pressing, preheated for 5 minutes in a hot press machine with a surface temperature of 180 ° C., and then repeatedly pressurized and depressurized to melt the sample and degas the residual gas in the sample, and then pressurized at 4.9 MPa and held for 5 minutes. After that, while applying a pressure of 4.9 MPa, the sample was gradually cooled at a rate of 10 ° C. / min, and when the temperature had dropped to near room temperature, the molded plate was removed from the mold. The obtained molded plate was conditioned for more than 48 hours in an environment with a temperature of 23 ± 2 ° C. and a humidity of 50 ± 5 ° C. A test piece in the shape of ASTM D1822 Type-S was punched out from the conditioned press plate to prepare a tensile impact strength test sample.

[0110] 2) Tensile impact strength test conditions The tensile impact strength was measured using the above test pieces with reference to JIS K 7160-1996 B method. The only difference from JIS K 7160-1996 was the shape of the test pieces. Other measurement conditions were performed in accordance with JIS K 7160-1996.

[0111] (9) Filling evaluation 1) The filling conditions The obtained laminate was filled with liquid under the following conditions using an automatic liquid filling and packaging machine (manufactured by Taisei Lamic Co., Ltd.). (Measurement conditions) Sealing temperature: (vertical) 163℃, (horizontal) 145~185℃ Packaging: Three-sided seal Bag dimensions: Width 75mm x Height 63mm pitch Filling: Water at 30℃ (filled at room temperature) Filling amount: approx. 15g Filling speed: 20m / min, 25m / min

[0112] 2) Criteria for determining filling suitability Filling was carried out under the above conditions while changing the transverse sealing temperature and filling speed, and the bag was evaluated for breakage, seal retraction, and water leakage by observing the appearance and under the pressure resistance conditions below. (Pressure resistance conditions) A load of 100 kg was applied for 1 minute using a pressure tester (manufactured by Komatsu Ltd.). (Evaluation Criteria) ◯: The transverse seal appearance was good, and the pressure resistance evaluation showed no breakage of the bag or water leakage, and no foaming was observed. ×: The transverse seal had a good appearance, but the pressure resistance evaluation showed bag breakage, setback, and water leakage. △: No breakage or water leakage in the pressure resistance evaluation, but wrinkles and bubbles were observed on the exterior of the horizontal seal.

[0113] 2.Resin materials [Example 1] (1) Synthesis of metal complexes 1) Synthesis of B-423 / Ni complex 1-1) Ligand B-423: Synthesis of 2-bis(2,6-dimethoxyphenyl)phosphano-6-(2,6-diisopropylphenyl)phenol

[0114] [ka] Ligand B-423 was synthesized according to the following scheme. In the following chemical formulas, -OMOM represents a methoxymethoxy group (-OCH2OCH3).

[0115] [ka]

[0116] 1-1-1) Synthesis of compound 2 It was synthesized according to patent document WO2010 / 050256.

[0117] 1-1-2) Synthesis of compound 3 To a solution of compound 2 (2.64 g, 10.0 mmol) in THF (5.0 ml) was added iso-PrMgCl (2 M, 5.25 ml) at 0° C. The reaction mixture was stirred at 25° C. for 1 h, and then PCl3 (618 mg, 4.50 mmol) was added at −78° C. The reaction mixture was warmed to 25° C. over 3 hours to give a yellow suspension. The solvent was removed under reduced pressure to give a yellow solid. This mixture was used in the next reaction without purification.

[0118] 1-1-3) Synthesis of compound 5 To a solution of compound 4 (30 g, 220 mmol) in THF (250 ml), n-BuLi (2.5 M, 96 ml) was added at 0° C. and stirred at 30° C. for 1 hour. i Pr)3 (123 g, 651 mmol) was added at -78°C, and the mixture was stirred at 30°C for 2 hours to give a white suspension. Hydrochloric acid (1M) was added to adjust the pH to 6 to 7, and the organic layer was concentrated to obtain a mixture. The resulting mixture was washed with petroleum ether (80 ml) to give 26 g of compound 5.

[0119] 1-1-4) Synthesis of compound 7 Compound 5 (5.00 g, 27.5 mmol), compound 6 (4.42 g, 18.3 mmol), Pd2(dba)3 (168 mg, 0.183 mmol), s-Phos(2-Dicyclohexylphosphino-2',6'-dimethoxybiphenyl) (376 mg, 0.916 mmol), and K3PO4 (7.35 g, 34.6 mmol) were weighed into a reaction vessel, and toluene (40 ml) was added. This solution was reacted at 110°C for 12 hours to obtain a black suspension. H2O (50 ml) was added and extracted with EtOAc (55 ml x 3). The organic layer was washed with brine (20 ml) and dried over Na2SO4. The organic layer was filtered, the solvent was distilled off under reduced pressure, and the residue was purified using a silica gel column to obtain 1.3 g of an oily substance.

[0120] 1-1-5) Synthesis of compound 8 To a solution of compound 7 (6.5 g, 22 mmol) in THF (40 ml), n-BuLi (2.5 M, 9.15 ml) was added dropwise at 0° C., the temperature was raised to 30° C., and the mixture was stirred for 1 hour. The reaction solution was cooled to −78° C., CuCN (2.1 g, 23 mmol) was added, and the mixture was stirred at 30° C. for 1 hour. The reaction solution was cooled to -78°C, and a solution of compound 3 (6.7 g, 20 mmol) in THF (40 ml) was added, followed by stirring at 30°C for 12 hours to obtain a white suspension. To the suspension was added H2O (50 ml) resulting in a white precipitate. The white precipitate was collected by filtration, dissolved in dichloromethane (20 ml), and aqueous ammonia (80 ml) was added thereto, followed by stirring for 3 hours. The product was extracted with dichloromethane (50 ml x 3), dehydrated with Na2SO4, and concentrated to obtain a yellow oily substance, which was purified with a silica gel column to obtain 2.9 g of compound 8.

[0121] 1-1-6) Synthesis of B-423 To a solution of compound 8 (2.9 g, 4.8 mmol) in dichloromethane (20 ml) was added HCl / EtOAc (4 M, 50 ml) at 0° C., and the mixture was stirred at 30° C. for 2 hours to give a pale yellow solution. The solvent was removed under reduced pressure, and dichloromethane (50 ml) was added. Washing with saturated aqueous NaHCO3 solution (100 ml) gave 2.5 g of B-423. The NMR assignment values ​​of the obtained ligand B-423 are shown below. (NMR) 1 H NMR (CDCl3, δ, ppm): 7.49 (t, 1H), 7.33 (t, 1H), 7.22 (m, 4H), 6.93 (d, 1H), 6.81 (t, 1H), 6.49(dd, 4H), 6.46(br, 1H), 3.56(s, 12H), 2.63(sept, 2H), 1.05(d, 6H), 1.04(d, 6H); 31 P NMR(CDCl3, δ, ppm):-61.6(s).

[0122] 1-2) Synthesis of B-423 / Ni complex All the following operations were carried out under a nitrogen atmosphere. Hereinafter, nickel acetylacetone will be referred to as Ni(acac)2. Ni(acac)2 (90.0 mg, 0.35 mol) was dissolved in toluene (30 mL) and added as a ligand to the B-423 (200 mg, 0.36 mmol) obtained above. The reaction solution was stirred at room temperature for 10 minutes, and the solvent was then removed under reduced pressure to give a deep red-purple solid. The product was washed with hexane (10 mL x 2) and dried under reduced pressure to obtain a reddish purple solid (yield: 247 g, 99%). The NMR assignment values ​​of the obtained metal complex are shown below. (NMR) 1 HNMR(C6D6,δ,ppm):7.65(d,1H), 7.25-7.35(m,3H), 7.07(t,2H), 6.97(d,1H), 6.51(t,1H), 6.2 6(d,4H), 4.83(brs,1H), 3.44(s,12H), 3.14(sept,2H), 1.44(d,6H), 1.29(s,6H), 1.21(d,6H).

[0123] (2) Manufacture of ionomers 1) Manufacturing Example 1 1-1) Preparation of ionomer-based resin precursor An ethylene / acrylic acid tBu copolymer was produced using transition metal complex B-423 / Ni. A precursor was produced with reference to Production Example 1 or Production Example 3 described in JP 2016-79408 A. The production conditions and production results, which were appropriately changed such as the metal catalyst type, metal catalyst amount, trioctyl aluminum (TNOA) amount, toluene amount, comonomer type, comonomer concentration, ethylene partial pressure, polymerization temperature, and polymerization time, are shown in Table 1, and the physical properties of the obtained precursor 1 are shown in Table 2.

[0124] 1-2) Manufacturing of ionomer-based resins Internal volume 1.6m 3In a SUS316L autoclave equipped with an agitator, 100 kg of the copolymer of Production Example 1, 2.0 kg of paratoluenesulfonic acid monohydrate, and 173 L of toluene were added and stirred at 105°C for 4 hours. 173 L of ion-exchanged water was added, stirred, and allowed to stand, and then the aqueous layer was extracted. Thereafter, the addition and withdrawal of ion-exchanged water was repeated until the pH of the extracted aqueous layer reached 5 or more. The remaining solution was added to a twin-screw extruder (L / D=42) equipped with a 42 mmφ vent device, and the solvent was distilled off by drawing a vacuum through the vent. Furthermore, the resin extruded continuously in the form of a strand from the die at the tip of the extruder was cooled in water and cut with a cutter to obtain resin pellets. In the IR spectrum of the obtained resin, the 850 cm -1 The disappearance of the peak near 1730 cm -1 The decrease in the peak near 1700 cm originates from the carbonyl group of the carboxylic acid (dimer). -1 An increase in the peak near As a result, decomposition of t-Bu ester and generation of carboxylic acid were confirmed, and ionomer base resin 1 was obtained. The physical properties of the obtained resin are shown in Tables 3 and 4. In the following tables, "E" and "AA" are abbreviations for "ethylene" and "acrylic acid", respectively, as structural units contained in the base resin.

[0125] 1-3) Production of ionomers 1-3-1) Preparation of Zn ion source Ethylene / methacrylic acid (MAA) copolymer (Mitsui Dow Polychemicals, brand: Nucrel N1050H) was continuously fed into a Toshiba Machine 26mmφ vented twin screw extruder (L / D=64) with a blending ratio of 54.5wt%, zinc oxide 45wt%, and zinc stearate 0.5wt%, and extruded under kneading conditions of barrel set temperature 150℃ and screw rotation speed 150rpm while removing gas and water generated during kneading from the vent part with a vacuum pump. Furthermore, the resin extruded continuously in the form of strands from the die at the tip of the extruder was cooled in water and cut with a cutter to obtain pellets as a Zn ion source.

[0126] 1-3-2) Preparation of ionomer Resin 1 and a Zn ion source were continuously fed into a Toshiba Machine twin-screw extruder (L / D=65) equipped with a 26mmφ vent device in a blending ratio that would give the desired degree of neutralization, and extrusion was performed under kneading conditions of barrel setting temperature 200°C and screw rotation speed 150 rpm, while injecting water at a ratio of 4 parts per 100 parts of the resin fed and removing gas and water generated during kneading from the vent part with a vacuum pump. Furthermore, the resin continuously extruded in the form of strands from the die at the tip of the extruder was cooled in water and cut with a cutter to obtain ionomer pellets. In the IR spectrum of the obtained resin, the 1700 cm -1 The peak at 1560 cm originating from the carbonyl group of the carboxylate group decreased. -1 The peak around 1700 cm originating from the carbonyl group of the carboxylic acid (dimer) increased. -1 From the reduction in the peak in the vicinity, it was confirmed that ionomer 1 with the desired degree of neutralization had been produced. The physical properties of the obtained ionomer 1 are shown in Tables 5 and 6.

[0127] (3) Preparation of laminates using ionomers A laminate was produced using ionomer 1 as the laminate resin composition. Using an extrusion laminating device, a biaxially oriented nylon film (Harden Film N2102, manufactured by Toyobo Co., Ltd.) with a width of 300 mm and a thickness of 15 μm was used as the base layer, and while a two-liquid anchor coating agent (Seikadyne solution, manufactured by Dainichiseika Chemicals Co., Ltd.) was applied thereon with a Bowes roll and ozone was sprayed in the laminating section, the laminate resin composition was coated as an intermediate layer to a thickness of 15 μm, and an ethylene-α-olefin copolymer composition (Kernel KC460S, manufactured by Japan Polyethylene Co., Ltd. (MFR: 8.0 g / 10 min, density: 0.905 g / cm) was coated as a sealant layer. 3)) was melt-extrusion laminated to a coating thickness of 25 μm. The extrusion lamination device was set so that the temperature of the resin extruded from the T-die attached to the extruder with a caliber of 40 mmφ was 290 ° C., and the extrusion amount was adjusted so that the coating thickness was the above thickness when the cooling roll surface temperature was 25 ° C, the die width was 400 mm, the die lip opening was 0.8 mm, and the take-up processing speed was 30 m / min. The processed laminate was aged in an oven at 40 ° C. for 48 hours, and then slit to a width of 150 mm to obtain a laminate for evaluation. The measurement results of filling suitability are shown in Table 7.

[0128] [Example 2] (1) Synthesis of metal complexes The same B-423 / Ni complex as in Example 1 was synthesized.

[0129] (2) Manufacture of ionomers 2) Manufacturing Example 2 2-1) Preparation of ionomer-based resin precursor In Production Example 1, the production conditions and production results were appropriately changed, such as the amount of metal catalyst, the amount of trioctyl aluminum (TNOA), the amount of toluene, the amount of comonomer, the ethylene partial pressure, the polymerization temperature, and the polymerization time, and the physical properties of the obtained precursor 2 are shown in Table 1.

[0130] 2-2) Manufacturing of ionomer-based resins Ionomer base resin 2 was obtained in the same manner as in Production Example 1. The physical properties of the obtained resin are shown in Tables 3 and 4.

[0131] 2-3) Production of ionomers Ionomer 2 was produced in the same manner as in Production Example 1, except that ionomer base resin 2 was used and the amount of Zn ion source was appropriately adjusted and added so as to achieve the desired degree of neutralization. The physical properties of the obtained ionomer 2 are shown in Tables 5 and 6.

[0132] (3) Preparation of laminates using ionomers A melt coextrusion lamination process was carried out in the same manner as in Example 1, except that ionomer 2 was used as the laminate resin composition instead of ionomer 1. The measurement results of the filling suitability are shown in Table 7.

[0133] [Comparative Example 1] The ionomer resin used was a copolymer of ethylene, methacrylic acid, and zinc methacrylate, produced by a high-pressure radical process (manufactured by Dow Mitsui Polychemicals, brand: HIMILAN HIM1652). The physical properties are shown in Tables 8 and 9.

[0134] - Preparation of laminates using ionomers Melt coextrusion lamination was carried out in the same manner as in Example 1, except that HIM1652 was used as the laminate resin composition instead of Ionomer 1. The measurement results of filling suitability are shown in Table 10.

[0135] [Comparative Example 2] Not an ionomer resin, mLLDPE for extrusion lamination (MFR: 8.5, density: 0.914g / cm 3 The physical properties are shown in Tables 8 and 9.

[0136] - Preparation of laminates using ionomers Melt coextrusion lamination was carried out in the same manner as in Example 1, except that mLLDPE was used as the laminate resin composition instead of ionomer 1. The measurement results of filling suitability are shown in Table 10.

[0137] [Table 1]

[0138] [Table 2]

[0139] [Table 3]

[0140] [Table 4]

[0141] [Table 5]

[0142] [Table 6]

[0143] [Table 7]

[0144] [Table 8]

[0145] [Table 9]

[0146] [Table 10]

[0147] <Consideration of the results of the Examples and Comparative Examples> As can be seen from Tables 7 and 10, the Examples had better appearances when filled than the Comparative Examples, and were capable of high-speed liquid filling over a wide range of transverse sealing temperatures from low to high. This is believed to be because the ethylene-based ionomer of the present invention has a substantially linear molecular structure, unlike conventional ionomers. [Industrial Applicability]

[0148] The present invention is useful for packaging bags for liquids or viscous materials in automatic filling machines, and is particularly useful for various packaging films, since high-speed filling is possible over a wide range of sealing temperatures from low to high by using a resin composition for laminates containing an ethylene-based ionomer having specific composition and physical properties as an intermediate layer.

Claims

1. A resin composition for an intermediate layer of a laminate having at least (I) a base layer, (II) an intermediate layer, and (III) a sealant layer in this order, the resin composition for an intermediate layer being characterized by containing an ethylene-based ionomer having the following characteristic (a): (a) Absolute value of complex elastic modulus G measured by a rotational rheometer * = The phase angle δ at 0.1 MPa is 50 degrees to 75 degrees.

2. The intermediate layer resin composition according to claim 1, wherein the ethylene-based ionomer is an ethylene-based ionomer obtained by converting at least a portion of the carboxyl groups and / or dicarboxylic anhydride groups in a copolymer (P) containing, as essential constituent units, a structural unit derived from ethylene, or a structural unit (A) derived from ethylene and an α-olefin having 3 to 20 carbon atoms, and a structural unit (B) derived from a monomer having a carboxyl group and / or a dicarboxylic anhydride group, into a metal-containing carboxylate containing at least one metal ion selected from Group 1, Group 2, or Group 12 of the periodic table.

3. The copolymer (P) 13 3. The resin composition for an intermediate layer according to claim 2, wherein the number of methyl branches calculated by C-NMR is 50 or less per 1,000 carbon atoms.

4. 4. The resin composition for an intermediate layer according to claim 2, wherein the copolymer (P) contains the structural unit (B) in an amount of 2 to 20 mol % in the copolymer.

5. The intermediate layer resin composition according to any one of claims 2 to 4, wherein the structural unit (A) is a structural unit derived from ethylene.

6. The intermediate layer resin composition according to any one of claims 2 to 5, characterized in that the copolymer (P) is produced using a transition metal catalyst containing a transition metal of Groups 8 to 11 of the periodic table.

7. 7. The intermediate layer resin composition according to claim 6, wherein the transition metal catalyst is a transition metal catalyst comprising a phosphorus sulfonic acid or phosphorus phenol ligand and nickel or palladium.

8. A laminate comprising at least (I) a substrate layer, (II) an intermediate layer, and (III) a sealant layer laminated in this order, and the intermediate layer (II) contains the intermediate layer resin composition according to any one of claims 1 to 7.

9. A liquid packaging product using the laminate according to claim 8.

Citation Information

Patent Citations

  • Cover material for sealed package

    JP1985056549A

  • Treatment of volatile acids

    JP1990004425A

  • Laminating resin composition

    JP1995026079A

  • Polyethylene composition for composite film, and composite film

    JP1996269270A

  • Laminating co-extrusion multilayer film and its manufacture

    JP1998323948A